STUDI FENOMENOLOGI PERAN PEMBELAJARAN DARING DALAM MASA PANDEMI COVID-19 - naning noviana; M. Riadhos Solichin; Vina Budiarti (Prodi Pendidikan Bahasa dan Sastra Indonesia IKIP WIDYA DARMA, 2022)
Conditions in various parts of the world that are experiencing a pandemic period due to the spread of the corona virus have caused massive changes in various fields. Even the world of education cannot avoid and be affected by the pandemic. According to Dikbud's instructions, the learning process in schools at all levels of education is carried out by distance learning (PJJ) using internet or online media. This study aims to determine the role of online learning during the COVID-19 pandemic on student learning. The population of this study were students of class XII Accounting at SMK Kemala Bhayangkari 1 Waru. Sampling was taken by purposive sampling so that the sample used was 22 students as respondents. Based on the results of interview analysis, it was concluded that students as research objects felt the direct impact of online learning. Students as research objects feel fear and anxiety, students also know the dangers of epidemics, students also gain online learning by using Whatsapp, zoom, and Quizziz applications.